Effect of Ascorbic Acid Dip Treatment on Frozen Storage of Squid (Loligo duzzaucelii, Orbigny) - Selvaraj, P.; Indira Jasmine, G.; Jeyachandran, P. (Fishery Technology, 2025)
Squid (Loligo duvaucelii) was treated with 0.5% ascorbic acid solution for 10 min and both treated and control samples were frozen at -40Â°C and stored at -20Â°C The quality changts during frozen storage and shelf life were evaluated by following the physical, chemical, bacteriological and sensory characteristics. Ascorbic acid treatment was found to improve the quality and shelf life compared to control.